Increasing Driving Range In Battery Electric Vehicle - et. al., Dr.M.Senthil Kumar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Electric vehicles are now developing as a replacement or alternative of a gasoline or diesel powered vehicle. As battery is the important part of battery electric vehicle, the other petroleum vehicles are becoming replaceable. This paper gives the solution to increase battery driving range by taken into account of two batteries. The electrical vehicle is designed using MATLAB/Simulink. The motor ratings and battery ratings are determined to design the electric vehicle. The two vehicles are designed one with lead acid battery and another with lithium ion battery. The permanent magnet synchronous motor is used, because of it has high efficiency than other motors. The speed of car, torque, power are determined and the distance is calculated. The comparison of vehicle with two different batteries are modelled and its distance were calculated.